2004
DOI: 10.1080/02699200410001663344
|View full text |Cite
|
Sign up to set email alerts
|

Single‐word intelligibility in speakers with repaired cleft palate

Abstract: Many speakers with repaired cleft palate have reduced intelligibility, but there are limitations with current procedures for assessing intelligibility. The aim of this study was to construct a single-word intelligibility test for speakers with cleft palate. The test used a multiple-choice identification format, and was based on phonetic contrasts which are problematic for speakers with cleft palate. Fifteen Cantonese speakers with repaired cleft palate served as speakers. The intelligibility score of each spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…There have been a number of studies examining intelligibility in older children and adults with CLP, although none have examined children less than 3 years ( [41,42] for reviews). Whitehill and Chau [43] studied the correlation between the production of high pressure consonants and intelligibility in individuals with CLP. This study found that stop consonants were among those highly correlated with intelligibility.…”
Section: The Role Of Babbling Complexity In Predicting Later Speech Amentioning
confidence: 99%
“…There have been a number of studies examining intelligibility in older children and adults with CLP, although none have examined children less than 3 years ( [41,42] for reviews). Whitehill and Chau [43] studied the correlation between the production of high pressure consonants and intelligibility in individuals with CLP. This study found that stop consonants were among those highly correlated with intelligibility.…”
Section: The Role Of Babbling Complexity In Predicting Later Speech Amentioning
confidence: 99%
“…Reduced intelligibility is often evident in the speech of individuals with cleft lip and palate (CLP; Whitehill and Chau, 2004), which is a craniofacial developmental abnormality that affects approximately one in every 500 to 1000 births (Peterson-Falzone et al, 2010). Speech difficulties, including abnormal resonance (e.g., hypernasality), audible nasal air emissions, nasal turbulence, and articulation errors, are frequent in this population.…”
mentioning
confidence: 99%
“…, Morris et al . , Whitehill and Chau , Wilson and Spaulding , Zajac et al . ) and sometimes adults (Borrie et al .…”
Section: Introductionmentioning
confidence: 99%
“…, McAuliffe et al . , Sussman and Tjaden , Whitehill and Chau ), with dysarthria due to cerebral palsy (Hustad and Beukelman , Hustad and Cahill , Hustad , Hustad et al . ) or neurological diseases (Borrie et al .…”
Section: Introductionmentioning
confidence: 99%